Direct measurement of three different deformations near the ground state in an atomic nucleus - Adrian Montes Plaza; Janne Pakarinen; Philippos Papadakis; Rolf-Dietmar Herzberg; Rauno Julin; Tomás R. Rodríguez; Andrew D. Briscoe; Andrés Illana; Joonas Ojala; Panu Ruotsalainen; Eetu Uusikylä; Betool Alayed; et al. (Communications Physics)
Abstract Atomic nuclei serve as prime laboratories for investigations of complex quantum phenomena, where minor nucleon rearrangements cause significant structural changes. 190Pb is the heaviest known neutron-deficient Pb isotope that can exhibit three distinct shapes: prolate, oblate, and spherical, with nearly degenerate excitation energies. Here we report on the combined results from three state-of-the-art measurements to directly observe these deformations in 190Pb. Contrary to earlier interpretations, we associate the collective yrast band as predominantly oblate, while the non-yrast band with higher collectivity follows characteristics of more deformed, predominantly prolate bands. Direct measurement of the $$E0({0}_{2}^{+}→ {0}_{1}^{+})$$ E 0 ( 0 2 + → 0 1 + ) transition and γ-e − coincidence relations allowed us to locate and firmly assign the $${0}_{2}^{+}$$ 0 2 + state in the level scheme and to discover a spherical $${2}_{3}^{+}$$ 2 3 + state at 1281(1) keV with $$B(E2;{2}_{3}^{+}→ {0}_{1}^{+})=1.2(3)$$ B ( E 2 ; 2 3 + → 0 1 + ) = 1.2 ( 3 ) W.u. These assignments are based purely on observed transition probabilities and monopole strength values, and do not rely on model calculations for their interpretation.